Analysis of Students’ Perceptions Impacted by The COVID-19 Pandemic about Implementation of Quizizz in Microbiology Courses - Adam Fernando; Diah Putri Anggun (IJER (Indonesian Journal of Educational Research), 2023)
Students are using the Quizizz application for the first time in a Microbiology course, so it is necessary to know their response regarding using this application. The purpose of this study was to describe the responses of students affected by the COVID-19 pandemic regarding the use of Quizizz while attending Microbiology lectures. This research is descriptive. This research was conducted in the January-June 2021 and 2022 semesters. This research involved 79 students of the 2019 and 2020 batches of Raja Ali Haji Maritime University who had taken online Microbiology courses. This study used a questionnaire distributed via Google Forms after students attended Microbiology lectures with the Quizziz application until the end of the semester. The number of questionnaire items given was 18, which were grouped into three aspects: 1) easiness of the application, 2) available benefits, and 3) unique benefits felt by students during and after the COVID-19 pandemic. Based on the results, the response of students affected by the COVID-19 pandemic related to the use of Quizizz while attending Microbiology courses is in a good category.